2005
DOI: 10.1152/ajpregu.00139.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activity rhythm of golden hamster (Mesocricetus auratus) can be entrained to a 19-h light-dark cycle

Abstract: Both temporary access to a running wheel and temporary exposure to light systematically influence the phase producing entrainment of the circadian activity rhythm in the golden hamster (Mesocricetus auratus). However, precise determination of entrainment limits remains methodologically difficult, because such calculations may be influenced by varying experimental paradigms. In this study, effects on the entrainment of the activity pattern during successive light-dark (LD) cycles of stepwise decreasing periods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…The present estimate of the lower range of entrainment in wt animals is similar to those of Pittendrigh and Daan (1976b) and Carmichael et al (1981), although light intensity, photophase duration, and other aspects of the procedure may affect this value (Boulos et al, 2002;Chiesa et al, 2005 andGorman et al, 2005). The present estimate of the lower range of entrainment in wt animals is similar to those of Pittendrigh and Daan (1976b) and Carmichael et al (1981), although light intensity, photophase duration, and other aspects of the procedure may affect this value (Boulos et al, 2002;Chiesa et al, 2005 andGorman et al, 2005).…”
Section: Range Of Entrainmentsupporting
confidence: 57%
“…The present estimate of the lower range of entrainment in wt animals is similar to those of Pittendrigh and Daan (1976b) and Carmichael et al (1981), although light intensity, photophase duration, and other aspects of the procedure may affect this value (Boulos et al, 2002;Chiesa et al, 2005 andGorman et al, 2005). The present estimate of the lower range of entrainment in wt animals is similar to those of Pittendrigh and Daan (1976b) and Carmichael et al (1981), although light intensity, photophase duration, and other aspects of the procedure may affect this value (Boulos et al, 2002;Chiesa et al, 2005 andGorman et al, 2005).…”
Section: Range Of Entrainmentsupporting
confidence: 57%
“…Finally, when various durations of light pulses were used, the maximum phase advance shown in C57 mice never exceeded 2 to 3 h (Schwartz and Zimmerman 1990; Comas et al 2006), leading to the prediction that 22 h would be the lower limit of the entrainment range. Combined, the summarized experiments conclude that entrainment to T18, which requires a daily decrease of nearly 6 h from the free-running period, even when animals are housed in apparent optimal conditions (i.e., singly housed with wheel; Cambras et al 2000; Chiesa et al 2005), is unprecedented.…”
Section: Discussionmentioning
confidence: 96%
“…This range of entrainment, however, can be markedly extended by exposure to dim light at night (compared with complete darkness) at an illuminance comparable to starlight or dim moonlight (Boulos et al 2002; Gorman et al 2005; Gorman et al 2006), even though such low light levels have been reported to be too weak to shift the clock (Brainard et al 1982; Brainard et al 1984; Nelson and Takahashi 1991a; Nelson and Takahashi 1991b; Brainard et al 2001). With the incorporation of dim nighttime illumination, hamsters were successfully entrained to T-cycles up to 30 h (Gorman et al 2005) or as low as 19 h (Chiesa et al 2005).…”
mentioning
confidence: 99%
“…Wheel running has been shown to function as a feedback signal for the circadian clock, helping animals synchronize to shortened light–dark cycles (Chiesa et al. ). We found that volitional access to running wheel under ChrA, both prevented the forced desynchronization of locomotor activity rhythms and was accompanied by normal body weight gain, as compared to control animals under LD also allowed to access a running wheel.…”
Section: Discussionmentioning
confidence: 99%